Domesticating home networks - Brown, Anthony (2016)
This thesis addresses the following question: How should domestic networks be reinvented to support self-management by domestic users? It takes a user-centred design approach to redesign the underlying domestic network infrastructure to better fit domestic users. The overall aim of this work is to create user-centred mechanisms to support self-management of domestic networks by domestic users. Two areas of the domestic network are studied in detail, user-centred mechanisms for domestic network infrastructure control and user-centred presentations of network data.